2017
DOI: 10.1513/annalsats.201608-656bc
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine as a Renal Protective Agent in Septic Shock. A Secondary Analysis of a Randomized, Double-Blind, Placebo-controlled Trial

Abstract: In this post hoc analysis of a randomized controlled trial, patients with septic shock randomized to receive thiamine had lower serum creatinine levels and a lower rate of progression to RRT than patients randomized to placebo. These findings should be considered hypothesis generating and can be used as a foundation for further, prospective investigation in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 31 publications
0
60
0
Order By: Relevance
“…Furthermore, in a secondary analysis of this study the need for renal replacement therapy and the serum creatinine were greater in the placebo group. [105] Similarly, in a propensity matched observational study in patients with septic shock Woolum et al demonstrated that thiamine supplementation increased lactate clearance and decreased 28-day mortality. [106] Hydrocortisone, Ascorbic Acid and Thiamine (HAT) in Combination…”
Section: Thiaminementioning
confidence: 97%
“…Furthermore, in a secondary analysis of this study the need for renal replacement therapy and the serum creatinine were greater in the placebo group. [105] Similarly, in a propensity matched observational study in patients with septic shock Woolum et al demonstrated that thiamine supplementation increased lactate clearance and decreased 28-day mortality. [106] Hydrocortisone, Ascorbic Acid and Thiamine (HAT) in Combination…”
Section: Thiaminementioning
confidence: 97%
“…In addition, at this time we were aware that the treatment of thiamine-deficient septic patients with thiamine reduced their risk of death. 2 In a post-hoc analysis of the study by Moskowitz et al, 5 these investigators demonstrated that intravenous thiamine reduced the risk of acute kidney injury. In an experimental sepsis model thiamine deficiency was associated with greater oxidative stress and a greater inflammatory response.…”
Section: Responsementioning
confidence: 99%
“…4 A post hoc secondary analysis of this study found that thiamine supplementation mitigated the use of renal replacement therapy among all patients with septic shock, regardless of thiamine status (21% vs 3%; P ¼ .04). 5 Marik and colleagues 1 also reported a decrease in the need for renal replacement therapy among patients with acute kidney injury (10% vs 37%; P ¼ .02).…”
mentioning
confidence: 95%
“…Each component of this combination of therapies has been recently evaluated individually in septic shock patients. A prior pilot randomized trial found that the provision of thiamine to septic shock patients with elevated lactate attenuated organ dysfunction (particularly renal dysfunction) and reduced lactate levels and potentially mortality in those patients with baseline thiamine deficiency [ 7 , 8 ]. In addition, two small randomized trials of ascorbic acid vs placebo in sepsis have demonstrated improved clinical outcomes [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%